2021
DOI: 10.3389/fpls.2021.685679
|View full text |Cite
|
Sign up to set email alerts
|

Specific Physiological and Anatomical Traits Associated With Polyploidy and Better Detoxification Processes Contribute to Improved Huanglongbing Tolerance of the Persian Lime Compared With the Mexican Lime

Abstract: Huanglongbing (HLB) is presently a major threat to the citrus industry. Because of this disease, millions of trees are currently dying worldwide. The putative causal agent is a motile bacteria belonging to Candidatus Liberibacter spp., which is transmitted by psyllids. The bacteria is responsible for the synthesis of callose at the phloem sieve plate, leading to the obstruction of the pores that provide connections between adjacent sieve elements, thus limiting the symplastic transport of the sugars and starch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 70 publications
2
34
1
2
Order By: Relevance
“…Such trends were also observed in polyploid citrus under severe water deficit [31,48] or salinity stress [29]. Moreover, enhanced leaf gas exchange parameters were reported in 3x Persian Lime subjected to HLB stress [32]. These enhanced photosynthetic capacity was also related to morphological properties induced by polyploidy [27,49].…”
Section: Are Triploid Genotypes More Tolerant or Resilient To Water D...mentioning
confidence: 58%
See 2 more Smart Citations
“…Such trends were also observed in polyploid citrus under severe water deficit [31,48] or salinity stress [29]. Moreover, enhanced leaf gas exchange parameters were reported in 3x Persian Lime subjected to HLB stress [32]. These enhanced photosynthetic capacity was also related to morphological properties induced by polyploidy [27,49].…”
Section: Are Triploid Genotypes More Tolerant or Resilient To Water D...mentioning
confidence: 58%
“…Increased SOD and APX activities were also observed in clementine grafted onto tetraploid Carrizo citrange under natural chilling stress [69]. In the same way, stronger APX and CAT activities were recorded in triploid Persian lime, which favored the oxidative stress-induced HLB limitation [32]. Moreover, these authors reported that CAT activity was the key marker that differentiate the triploid Persian lime from 2x Mexican lime under HLB stress.…”
Section: Does Osmotic Adjustment Explain the Better Sustain Of Leaf W...mentioning
confidence: 77%
See 1 more Smart Citation
“…Indeed, polyploidy is considered a driving force in plant evolution and adaptation [ 43 ], and either auto- or allopolyploidization events have contributed to speciation and diversification [ 42 ]. Recent research has revealed the adaptive effect of polyploidy on plant response to global climate change as well as improving tolerance to plant pathogens [ 43 , 44 ]. Polyploidy also leads in woody plants to larger xylem and phloem conduits, lowering hydraulic resistance and facilitating long-distance transport between organs [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Persian lime is still considered one of the least susceptible to HLB when compared to sweet citrus such as orange (C. sinensis), tangerine (C. clementina), and even to other limes such as Mexican lime (C. aurantifolia), as Persian lime trees are able of continue their production for many years after CLas has been detected (Evans et al 2014). Recently, HLB diseased Persian lime treed maintained high physiological performance in terms of photosynthesis, stomatal conductance and transpiration (Sivager et al 2021), suggesting that phloem activity can be maintained in this species during HLB infection.…”
Section: Introductionmentioning
confidence: 99%